Liability of Housing Developers and Residents Relating to Environmental Management Dues - Arif Sandjaja; Mohammad Saleh (Journal of Law, Politic and Humanities, 2024)
The purpose of this study is to investigate the legal relationship that occurs between developers and housing residents during the process of buying and selling houses starting from the binding agreement for the sale and purchase of houses until the house is occupied. Furthermore, this study discusses the liability of developers and housing residents in the event of default or unlawful acts. The policy of shutting down clean water supply carried out by developers to residents is often not only related to the failure to pay Environmental Management Dues (IPL) bills which are combined with water bills, but also often associated with other things as an effort to suppress housing residents. From a legal perspective, the developer's actions can be categorized as unlawful. On the other hand, housing residents who are dissatisfied with the developer's services choose not to pay (IPL), where from the developer's perspective, the resident's actions are in default. This study will examine legal relations and legal resolution solutions related to conflicts over Environmental Management Dues between Developers and Housing Residents.